PERSEPSI DAN PERILAKU MASYARAKAT TERHADAP PRODUK HALAL KOSMETIK WARDAH DI KECAMATAN LEUWILIANG DAN KECAMATAN LEUWISADENG, KABUPATEN BOGOR - Siti Fauziah; Rully Trihantana; Bayu Purnama Putra (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
This study aims to determine the influence, and the relationship between people's perceptions and behavior towards Wardah's halal cosmetic products in Leuwiliang and Leuwisadeng Districts, Bogor Regency. This research is a quantitative research. The population in this study were users of wardah cosmetic products in Leuwiliang and Leuwisadeng Districts, Bogor Regency. Sampling using purposive random sampling technique. Data analysis techniques using descriptive analysis and inference analysis. The steps to prove the hypothesis in this study used multiple linear regression analysis, Simultaneous (F Statistical Test), Partial (t Statistical Test) and Chi Square Test. Based on the results of this study, people's perceptions and behavior simultaneously have a significant effect on Wardah's halal cosmetic products in Leuwiliang District and Leuwisadeng District, Bogor Regency. In addition, that between gender, age, use of more than one product, has nothing to do with people's perceptions and behavior towards Wardah's halal cosmetic products.